PENGARUH PRODUKSI, JUMLAH KEDATANGAN WISATAWAN, DAN KURS DOLLAR AS TERHADAP IMPOR MINUMAN BERALKOHOL KE BALI - Dharma, I Wayan Widya; Dewi, Ni Putu Martini (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
This research aim to determine the influence of the production of alcoholic beverages, number of tourist arrivals, and the US dollar exchange rate simultaneously and partially against the import of alcoholic beverages to Bali, and determine which  variables between the production, the tourist arrivals, and the US dollar exchange rate that dominantly influence the import of alcoholic beverages to Bali. This study uses natural logarithm secondary data with multiple linear regression analysis technique. Based on the results of this study simultaneously the production, the tourists arrivals, and US dollar exchange rate significantly influence the import of alcoholic beverages to Bali.  Partially the tourist arrivals has a positive and significant impact on import of alcoholic beverages to Bali, but the production and US dollar exchange rates did not significantly influence the import of alcoholic beverages to the Bali. Keyword : import of alcoholic beverages, production, number of tourist arrival, exchange rate.